Estudio de Bacillus subtilis como bacteria promotora de crecimiento vegetal en cultivos hortícolas en Los Ríos - Macías Palma, Klever Javier (2021)
The present investigation tarts on the study of Bacillus subtilis as a plant growth promoter bacteria in horticultural crops in Los Ríos. Among the growth-promoting bacteria is Bacillus, which is a genus used to control phytopathogens, and even pests, from which different commercial products have been formulated based on these bacteria. Due to the conclusions raised, it is determined that Bacteria promote plant growth through different direct and indirect mechanisms that induce systemic resistance of plants, both to biotic stress (attack by pathogens) or to abiotic stress (periods of drought, temperature, contaminants); Bacillus subtilis is a bacterium considered as an ecological alternative to improve fruit growth and increase the yield of horticultural crops, especially in the province of Los Ríos, since it produces natural antibiotics that weaken the cell wall and inhibit the growth of pathogens through production of substances such as Bacilomycin, Fengimycin and Micoceryn, which are considered antibiotics against fungi and genetic engineering is the science that allows obtaining genetically modified microorganisms that allows expanding capacities of growth-promoting bacteria